Incidence of Osteoporosis in Patients with Urolithiasis - Bijelic, Radojka (Med Arch, 2014)
INTRODUCTION. Clinical researches have shown an increased bone disintegration and lower bone mass in patients with calcium urolithiasis. GOAL. The goal of our research was to establish the incidence of osteoporosis in adult patients with calcium urolithiasis, on the basis of measuring mineral bone density, using DEXA method, with a special reflection on age subgroups. MATERIAL AND METHODS. Clinical research was prospective and it was implemented at the University Clinical Center of Banja Luka, at the Clinic for Endocrinology, Diabetes and Metabolic Diseases and at the Urology Clinic. Material in this research consisted of patients divided in two groups, a working and a control group. One hundred and twenty (120) patients were included in both these groups, divided in three age subgroups: 20-40, 40-60 and over 60. The working group consisted of the patients with calcium urolithiasis and the control group consisted of patients without calcium urolithiasis. Establishing of mineral bone density at L2-L4 of lumbal spine vertebrae and hip was done for the patients in both these groups, using DEXA method. RESULTS. Analysis of mineral bone density using DEXA method in patients in age groups of working and control groups, as well as in the total sample of working and control groups, have shown that the patients of the working group, over 60, had a decreased mineral bone density (30% of osteopenia and 15% osteoporosis) significantly more expressed when compared to the other two age groups (12.5% in the subgroup 20-40 and 17.5% in the subgroup 40-60), which presents a statistically significant difference (p<0.05). In the control group, when taking into account age groups, osteopenia and osteoporosis were marked in 37.5% and 2.5% in the group of patients over 60, whereas in the youngest population, 5% of osteopenia was found, which presents a statistically significant difference (p<0.05). When observing the total sample of working and control group, there was a statistically significant difference in the working and control group (p<0.01); incidence of osteoporosis in the working group amounted to 7.5% and in the control group it was 0.8%. CONCLUSION. Urolithiasis and osteoporosis are two multifactorial diseases which are evidently reciprocal. This is why we suggest that educating the population about the risk factors for occurrence of these diseases as well as preventive measures that may contribute to their decrease should begin as early as possible.